The Influence of Product Quality, Promotion, and Price on Purchasing Decisions at Dharmasraya Donut House: Pengaruh Kualitas Produk, Promosi, dan Harga Terhadap Keputusan Pembelian di Rumah Donat Dharmasraya - Angraini, Melpi; Mulya, Jumiatul (International Journal of Management and Business (IJMB), 2024)
This study aims to determine and analyze: the effect of Product Quality, Promotion, and price on purchasing decisions at Rumah Donat Dharmasraya. This type of research is quantitative research with Associative Design. Sampling technique using non purposive sampling. The number of samples used was 96 respondents. Data collection techniques used in this study is a survey technique using questionnaires as research instruments. The data analysis technique used is multiple linear regression analysis. The results of this study showed that partially the product quality variables have a positive and significant effect on purchasing decisions, promotional variables have a positive and significant effect on purchasing decisions, and price variables have a positive and significant effect on purchasing decisions. The value of R2 is 0.426. This can be interpreted that the quality of products, promotions, and prices affect the purchasing decision with a percentage of 42.6%, while the remaining 57.4% are influenced by other factors not examined in this study. Based on the analysis that has been tested, it can be concluded that the variables of Product Quality, Promotion, and price have a positive and significant relationship influence on purchasing decisions at Rumah Donat Dharmasraya.